The effect of chemical treatment, fibre length, fibre content and injection moulding parameters to uv irradiation resistance of oil palm fibre reinforced composites - Fitri, Muhamad (2019)
There are many types of polymer used in engineering materials expose to UV irradiation, such as automotive parts (car body, bumper, dashboard etc.) which can cause material degradation. Some polymers are used in pure polymer and some of them in composite material. This study has investigated the composite material degradation. In this study, polypropylene was used as a matrix of the composite material samples, while oil palm fibre as reinforcement. The effect of the fibre length, fibre content, fibre treatment, coupling agent and injection moulding parameter to ultraviolet (UV) light resistance of this composite and also the optimum setting of them were investigated. The UV resistance was examined via the change of mechanical properties after UV exposured in the UV accelerated weathering tester. The Linear regression models were generated for tensile strength, strain at maximum stress, break stress, break strain and Charpy Impact strength based on six different UV exposure time i.e.: 0, 96, 336, 504, 1008, and 1512 hours. The significance of the regression models were tested by Analysis Of Variance (ANOVA) and verified by two expose time i.e: 168 and 672 hours. This study found that all of the mechanical properties decrease after UV irradiated. The largest property decrease was break strain of the samples, which was decrease in the range 44.54% to 79.21% after 1512 hours UV irradiated. The lowest decrease was break stress in the range 27.38 % to 63.82%. It was also found in this study that fibre content, and UV irradiation time, significantly affect all properties. Coupling agent and alkali treatment significantly affect all properties except strain at maximum stress. Whereas fibre length and injection moulding parameter only significantly affect the Impact strength of the specimens. All of the regression models are significant which are signed by the p value of each of regression models were lower than 0.05. The equation for predicting the lifetime of UV exposed of oil palm fibre reinforced composite have been generated. The lifetime UV irradiated specimen can be predicted using this equation.